Independent Predictors of Mortality for Aeromonas Necrotizing Fasciitis of Limbs: An 18-year Retrospective Study - Huang, Tsung-Yu (Sci Rep, 2020)
Necrotizing fasciitis (NF) of the limbs caused by Aeromonas species is an extremely rare and life-threatening skin and soft tissue infection. The purpose of this study was to evaluate the specific characteristics and the independent predictors of mortality in patients with Aeromonas NF. Sixty-eight patients were retrospectively reviewed over an 18-year period. Differences in mortality, demographics data, comorbidities, symptoms and signs, laboratory findings, microbiological analysis, empiric antibiotics treatment and clinical outcomes were compared between the non-survival and the survival groups. Twenty patients died with the mortality rate of 29.4%. The non-survival group revealed significant differences in bacteremia, monomicrobial infection, cephalosporins resistance, initial ineffective empiric antibiotics usage, chronic kidney disease, chronic hepatic dysfunction, tachypnea, shock, hemorrhagic bullae, skin necrosis, leukopenia, band polymorphonuclear neutrophils >10%, anemia, and thrombocytopenia. The multivariate analysis identified four variables predicting mortality: bloodstream infection, shock, skin necrosis, and initial ineffective empirical antimicrobial usage against Aeromonas. NF caused by Aeromonas spp. revealed high mortality rates, even through aggressive surgical debridement and antibacterial therapies. Identifying those independent predictors, such as bacteremia, shock, progressive skin necrosis, monomicrobial infection, and application of the effective antimicrobial agents against Aeromonas under the supervision of infectious doctors, may improve clinical outcomes.